Impact of dental treatment on self-esteem and oral health selfperception of children and adolescents victims of sexual abuse - Mariz, Ana Luísa de Ataíde; Araújo, Symonne Leandro; Negrinho, Luiz Antônio; Pedrosa, Marlus da Silva; Pompeu, José Guilherme Férrer; da Silva, Cláudio Heliomar Vicente (Brazilian Dental Science, 2018)
Objective: To evaluate the oral health self-perception and the influence of dental treatment on the multidisciplinary approach of adolescent victims of sexual abuse. Material and Methods: It was adopted a qualitative methodology that emphasized the deepening and comprehension of the answers obtained. Six adolescents, from both genders, victims of sexual abuse in the last two years, aged between 10 and 15, took part of the study. A questionnaire was applied before and after the dental treatment in order to evaluate changes in the self-perception and self-esteem of the individuals. The answers were categorized into two thematic axes with the use of the qualitative content analysis: self-perception and self-esteem. Psychological attendance prior and after the dental interventions enabled to comprehend the changes observed. Results: The participants presented a coherent self-perception in relation to the present clinical situation and an increase of their self-esteem after the dental interventions. Conclusion: Dental treatment contributed to improvements regarding self-esteem and oral health self-perception in victims of sexual abuse. Keywords Self-reported oral health; Sexual abuse; Dental aesthetic; Adolescent; Child.